2013
DOI: 10.1016/j.neuroimage.2012.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Shared electrophysiology mechanisms of body ownership and motor imagery

Abstract: Although we feel, see, and experience our hands as our own (body or hand ownership), recent research has shown that illusory hand ownership can be induced for fake or virtual hands and may be useful for neuroprosthetics and brain-computer interfaces. Despite the vast amount of behavioral data on illusory hand ownership, neuroimaging studies are rare, in particular electrophysiological studies. Thus, while the neural systems underlying hand ownership are relatively well described, the spectral signatures of bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 97 publications
2
57
1
Order By: Relevance
“…A recent paper (Evans and Blanke, 2013) showed that synchronous visual-tactile feedback during the hand ownership illusion generates mu-ERD in the sensorimotor cortex similar to the one produced during motor imagery BCI. Although, in our experiment no tactile feedback was provided, we postulate that their results are compatible with our findings and suggest that the correlations found in the current experiment between the mu-ERD and P450 with the ownership illusion question may be related by a similar mechanism to the one they describe.…”
Section: Discussionmentioning
confidence: 80%
“…A recent paper (Evans and Blanke, 2013) showed that synchronous visual-tactile feedback during the hand ownership illusion generates mu-ERD in the sensorimotor cortex similar to the one produced during motor imagery BCI. Although, in our experiment no tactile feedback was provided, we postulate that their results are compatible with our findings and suggest that the correlations found in the current experiment between the mu-ERD and P450 with the ownership illusion question may be related by a similar mechanism to the one they describe.…”
Section: Discussionmentioning
confidence: 80%
“…Neuroimaging studies (Macaluso and Driver, 2005;Makin et al, 2007;Serino et al, 2011a;Sereno and Huang, 2014) associated these effects with brain regions in human posterior parietal and premotor cortices, hosting bimodal and multimodal neurons, as revealed by earlier neurophysiological work in non-human primates (Duhamel et al, 1998;Graziano et al, 1994;Rizzolatti et al, 1981). Similar regions also process signals involved in self-attribution of the hand (Ehrsson et al, 2004;Tsakiris et al, 2007;Evans and Blanke, 2013) and face (Cardini et al, 2011;Apps et al, 2015).…”
Section: Introductionmentioning
confidence: 73%
“…In the ''virtual arm illusion,'' spatial and temporal synchrony is created between the touch applied to the participant's hand (top part of the figure) and the touch observed on the virtual arm (bottom part of the figure: scene shown in the head-mounted display). Reproduced from Evans and Blanke [110]. Shared electrophysiology mechanisms of body ownership and motor imagery.…”
Section: Investigating Body Part Representationsmentioning
confidence: 99%